2001
DOI: 10.1051/forest:2001123
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the impact of climate and disturbances on tree-rings of Fagus sylvatica L. and Quercus robur L. in a lowland forest in Cantabria, Northern Spain

Abstract: -The influence of climate and disturbances on tree-ring widths of European beech and pedunculate oak were evaluated in a lowland forest of Northern Spain. From 1925 to 1980, 36% of the variance of beech ring-width and 29% of the oak one was explained by climate. The climatic models showed that low precipitation in July of the previous year limited the radial growth of beech, while oak one was instead restricted by water deficits in July of the current year. Ten main disturbance periods were identified from 178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
2
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 31 publications
8
78
2
12
Order By: Relevance
“…A stronger correlation can probably be achieved by using daily climatic data grouped into periods of different lengths [5,17,29]. Even if low, the percentage of explained variance is within the usual range in other Europe localities [5,8,27,35,38,44,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A stronger correlation can probably be achieved by using daily climatic data grouped into periods of different lengths [5,17,29]. Even if low, the percentage of explained variance is within the usual range in other Europe localities [5,8,27,35,38,44,49].…”
Section: Discussionmentioning
confidence: 99%
“…Autoregressive modeling of the residuals and biweight robust estimation of the mean were used to calculate chronology indices for each ring component [11,44]. These master chronologies were used to evaluate the radial growth-climate relationships.…”
Section: Sampling Measurements and Computation Of Chronologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is usual in arid regions (i.e. Mediterranean region) (Rozas 2001;Andreu et al 2007), similar effects have recently been observed also for trees growing in boreal regions (Wilmking et al 2004). Thus, knowledge on climate growth relationships, considering regional variability (Andreu et al 2007), is necessary.…”
Section: Introductionmentioning
confidence: 88%
“…speed of cell division, differentiation and elongation) (Pallardy 2008) and assimilation (Berry and Downtown 2012), which affects growth, particularly in the second part of growing period (Barbaroux and Breda 2002). The amount of precipitation, which is often significant for tree growth in southern and central parts of specie's distribution area (Rozas 2001;Kelly et al 2002;Jansons et al 2013), did not show significant effect on HI of hybrid aspen ( Table 1), suggesting that the availability of water was not limiting height growth throughout the entire vegetation season. Probably, precipitation might be significant for HI in June-August, when temperature is the highest (Fig.…”
Section: Discussionmentioning
confidence: 99%